Analisis Aspek Pemasaran UMKM di Masa Resesi Global Dampak Dari Pandemi Covid-19 - Hanung Eka Atmaja; Ivo Novitaningtyas (Jurnal Ilmiah Poli Bisnis, 2021)
The Covid-19 pandemic that occurred globally has an impact on various sectors in Indonesia including the MSMEs sector. Based on these conditions, a marketing strategy is needed for MSMEs in Indonesia to be sustainable. The research aims to analyze and describe marketing strategies for MSMEs to survive in the Covid-19 pandemic condition. This research uses exploratory qualitative analysis with participatory observation techniques. This research uses primary data from observations and secondary data from previous studies. The results recommend MSMEs to sell their products via e-commerce and promote via digital marketing as a marketing strategy. Moreover, MSMEs need to optimizing customer marketing relationships in order to create a loyal customer. Loyal customers have the potential to make repeat purchases and recommend products to other potential consumers. By implementing this strategy, it is hoped that the MSME business will continue to survive and have a positive impact on society and the economy.